A strengths-based approach to widening participation students in higher education. Issue 2 (12th June 2017) - Krutkowski, Sebastian
Abstract : Purpose: The purpose of this paper is to highlight the need for a pedagogical shift from "problems" to "possibilities", which will help ease the transition of students into higher education (as well as the transitions between levels of study and employment), especially those coming from under-represented and under-privileged backgrounds, known in the UK as the widening-participation category. Design/methodology/approach: GSM London is the first higher education provider in the UK to implement a strengths-based approach to staff and student development. This study looks at the delivery plan for strengths-based education, especially how it can inform and reshape information literacy instruction in the library and other academic skills modules. Findings: Higher education is an important environment to help learners develop their talents into strengths, which can be defined as "the ability to provide consistent and near-perfect performance in a given activity" (Buckingham and Clifton, 2005, p. 20). There is a perception that widening-participation students have more significant gaps or weaknesses upon entering university education. This case study confirms that not remediation but a strengths-based approach has the strongest potential to enable students to better manage their weaknesses and become independent learners. Research limitations/implications: Further research is required, as not enough empirical data could be collected after only one semester of strengths-based learning implementation at GSM. Originality/value: The author attempts to re-conceptualise information literacy instruction and propose a mapping exercise, in which library instruction is aligned to the principles of strengths-based education and the language of 34 themes in the popular strengths assessment tool from the Gallup organisation. The expectation is to build fluid transitions between levels of study and academic matters and extracurricular activities that students take part in. This approach can also assist learners far beyond the library and long after they leave university, equipping students with a skillset that enables a more meaningful participation in society.